A City‐wide Investigation of the Isotopic Distribution and Source of Tap Waters for Forensic Human Geolocation Ground‐truthing1. Issue 3 (1st December 2016) - Ueda, Momoko; Bell, Lynne S.
Abstract: Human geolocation is prefaced on the accuracy of the geographic precision of mapped isotopic values for drinking water. As most people live in cities, it becomes important to understand city water supplies and how the isotopic values uniquely reflect that city. This study investigated the isotopic distribution of δ 2 H and δ 18 O from sourced tap waters that were collected from across the Metro Vancouver (MV) area ( n  = 135). The results revealed that the isotopic values reflect their water sources with a range of 5.3‰ for δ 18 Otap and 29.3‰ for δ 2 Htap for MV. The results indicate that individual cities need higher resolution studies to determine their tap water isotopic ranges, and a good understanding of the water supply network itself for human geolocation work. With an extended high‐resolution understanding of each city, human tissue may be compared with more certainty for geolocation.